Komposisi Jenis dan Regenerasi Alami Mangrove Di BKPH Ujung-Krawang, KPH Bogor, Jawa Barat - Cecep Kusmana; Yustika Siregar (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2020)
The mangrove forests in BKPH Ujung-Krawang is a protected forest that has been degraded by human activities. This study aims to identifying the species composition and elucidating the structure and regeneration mangrove forests in BKPH Ujung-Krawang, KPH Bogor, West Java. This research carries out in two location (Muara Gembong and RPH RPH Singkil), with the condition of mangrove forests are degraded due to the forest conversion into fishpond, fish farming, and housing areas on large scale. Mangrove forest composition consisted by api-api (Avicennia sp.), pedada (Sonneratia sp.) and buta-buta (Excoecaria agallocha). Based on observation, mangrove forests regeneration in RPH Muara Gembong categorized as “good “caused number of seedlings is more than sapling and “fair” in RPH Singkil caused number trees is greater than the level of the regeneration (sapling and seedling). Keywords: KPH Bogor, mangrove forest, natural regeneration, species composition, Ujung-Krawang